Perceptions on the Use of Movies and Multimodal Aspects for Teaching Conversational Competence to Porter Students - Arief Eko Priyo Atmojo (ELT Worldwide: Journal of English Language Teaching, 2021)
This study addresses these following questions: (1) How are the students’ and teachers’ perceptions toward the use of movies to teach conversational competence to porter students in a vocational high school?; (2) How are the students’ and teachers’ perceptions toward the use of movies to facilitate the students’ understanding of verbal and non-verbal conversational competence in the target situation of the job they will encounter as porters?; and (3) How can multimodal aspects help the students to master the conversational competence needed to become porters as reflected on the movies used in this study? This study employs descriptive qualitative design. The results show that movies are perceived to improve the conversational competence of porter students in a vocational high school. Movies facilitate the students’ understanding of verbal and non-verbal conversational competence in the target situation of the job they will encounter as a porter. The multimodal aspects help the students to master the conversational competence needed to be a porter as reflected on the movies. Therefore, movies along with their multimodal aspects are worthy for teaching conversational competence to porter students.